O ciclo de maré influencia a dinâmica de microplásticos em um estuário do semi-areado brasileiro? - Alves, Ravena Santiago (2024)
Microplastics (MPs) are synthetic polymers ranging in size from 1 μm to 5 mm, which are considered contaminants of growing global environmental concern, due to their wide distribution in the environment and because they threaten marine life. Estuaries are recognized as one of the main routes for MPs to enter the oceans. However, it is still necessary to understand how hydrodynamic and climatic factors influence its transport. In this context, the objective of the research is to evaluate the influence of tidal fluctuations and seasonality on the abundance and morphological characteristics of MPs in the surface waters of the Cocó River estuary (Fortaleza – CE). Collections took place at a fixed point near the mouth of the river, every 2 hours throughout a tidal cycle, covering three samples at ebb tide and three at flood tide, during two seasonal seasons (rainy and dry), in spring tide conditions. Surface water sampling was done through 1-min trawls, using a plankton net (120 μm mesh), positioned next to the boat and kept floating to collect the first 15 cm of the surface. The material retained in the collection cup was transferred to glass jars and stored at -20 oC until analysis. The samples were processed through sieving through a 5 mm and 63 μm mesh, digestion of the organic matter with 10% KOH, separation of particles by density difference with ZnCl2 (1.6 g/cm3 ) and filtration on glass fiber filters (0.7 μm porosity). The filters were viewed under a stereomicroscope to count and classify the MPs by shape, size and color. The abundance of MPs in surface waters varied throughout the daily tidal cycle from 11.0 to 32.5 items/m3 in the rainy season and from 12.4 to 40.0 items/m3 in the dry season, decreasing this concentration during the ebb tide and increasing at the flood tide, in both seasonal seasons. However, the average abundance of MPs did not vary significantly between the rainy (21.2 ± 8.7 items/m3) and dry (22.9 ± 11.3 items/m3) seasons. The predominant forms were fibers (50%), films (25%), rubbers (13%) and fragments (10%). The predominant size classes were 0.5 – 1.0 mm (29%), 0.12 – 0.30 mm (23%), 0.3 – 0.5 mm (20%) and 1 – 2 mm (20%). The main colors were transparent (32%), white (22%), black (21%) and blue (15%). Identifying possible patterns of MPs dynamics during a tidal cycle could provide measures to estimate the rates of MPs transported from the river to the ocean and vice versa, determine the best time for more representative sampling, and adopt pollution control strategies.